2022
DOI: 10.1093/ntr/ntac004
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Mental Health Professionals, Patients, and Carers’ Perceived Barriers and Enablers to Supporting Smoking Cessation in Mental Health Settings

Abstract: Introduction Evidence-based smoking cessation and temporary abstinence interventions to address smoking in mental health settings are available, but the impact of these interventions is limited. Therefore, this review aimed to identify and synthesise the perceived barriers and enablers to supporting smoking cessation in mental health settings. Method Six databases were searched for articles reporting the investigation of perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 86 publications
1
15
0
Order By: Relevance
“…Many people also describe using smoking as a method to “self-medicate” mental health symptoms, such as depression or anxiety ( 19 , 27 , 62 ). This view is persistent among many populations, including health professionals ( 20 , 21 ). Therefore, the MHWLs contradict peoples’ current understanding of the effects of smoking, and the effects of smoking on mental health are not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many people also describe using smoking as a method to “self-medicate” mental health symptoms, such as depression or anxiety ( 19 , 27 , 62 ). This view is persistent among many populations, including health professionals ( 20 , 21 ). Therefore, the MHWLs contradict peoples’ current understanding of the effects of smoking, and the effects of smoking on mental health are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…There is an extensive range of physical health risks portrayed on tobacco health warning labels in the UK and internationally (16), which are demonstrated to be effective in promoting smoking cessation, and reducing smoking uptake (14,17,18). However, it is less well known amongst the general public and healthcare professionals that smoking can negatively affect mental health (19)(20)(21). A large body of evidence suggests that tobacco use increases the risk of developing depression, schizophrenia and bipolar disorder (22)(23)(24)(25), and that smoking cessation can reduce symptoms of depression, anxiety, and stress, and lead to improved wellbeing and positive feelings (26).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, high smoking rates in mental health settings constitute a smoking culture with “a long and entrenched history” [ 17 ], which affect healthcare professionals through peer pressure, and inevitably influence psychiatric patients through role modelling. It was pointed out that frequent observations of smoking professionals and other patients challenged patients’ own attempts to quit this unhealthy habit [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, Prochaska (2011) reported that smoking cessation interventions are still not offered often enough to patients in mental health facilities [ 54 ]. A recent review reported that the lack of awareness among healthcare professionals regarding links between tobacco use and mental illness remains a serious barrier to the provision of smoking cessation support [ 51 ]. Prochaska (2010) argued that smoking, contrary to professional belief, does not help relieve negative mental health symptoms, and is actually associated with increased depressive symptoms and suicidal risk behaviours [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…These were then coded to the domains of the COM-B and TDF. The detailed methods are published elsewhere 25 .…”
Section: Stage One: Understanding the Behaviour And Identifying 'What...mentioning
confidence: 99%